Efficacy & Significance of LYSO HERB Herbal Lysine in the nutrition, metabolism and health in Poultry & Efficacy and significance of the phytogenic METHO ADD Herbal Methionine as replacer of Synthetic DL- Methionine in nutrition and health of Poultry - Gudipati, Sujani (Revista Sistemática, 2024)
In poultry industry, amino acids are supplied along with vitamins and minerals since these play a pivotal role as protein building units which are the essentialities of growth and metabolism. Of the 9 essential amino acids Methionine is the first limiting one followed by Lysine, these cannot be synthesized by animals hence to be obtained from external sources majorly the feed.Amino acids act as intermediates in all the metabolic and physiological functions of the bird like calcium absorption, production of collagen, antibodies, hormones, enzymes. Their deficiency causes de-pigmentation, reduced hemoglobin, poor FCR, reduced production, retarded growth, poor feathering and egg production, immune suppression and increased disease incidence. Cells in the body are constantly being broken down and restored, so the body needs these amino acids to produce new hormones and restore the body.Of late the use of synthetic Lysine and Methionine as supplement has increased due to high demand of meat. The safety of these is questionable due to   higher pricing, emergence of drug resistance, residual toxicity and other side effects. Therefore, a renewed interest in developing natural alternatives to maintain production, performance and health in poultry,  hence Phytogenic herbals are considered the best option..The results obtained here provide clear evidence of the potential of  Phytogenic Herbal  Lysine as  Lyso  Herb  and  Herbal Methionine  as Metho Add as substitute of synthetic Lysine &  Methionine with unaltered activity throughout, without reducing growth performance, increasing fat accretion and changing serum biochemical characteristics, with better performance and economics.